THE PSYCHOLOGICAL PRINCIPLES OF FAMILY EDUCATION IMPACT ON SENIOR PRESCHOOLERS’ EMOTIONAL DEVELOPMENT - Honcharuk, Nataliia; Onufriieva, Liana (PSYCHOLOGICAL JOURNAL, 2019)
The article envisages the psychological principles of studying on the styles of family education and their influence on senior preschoolers’ emotional development. The features of preschoolers’ emotional development in the conditions of family education are described. On the basis of the analysed theoretical scientific sources, it is assumed that children’s emotional development depends on the style of family education used by their parents in everyday interaction. The main styles of family education were identified with the performed experimental study, particularly, the styles of non-interference; competition; moderation; warning; control; compassion; and a harmonious style. The essence of each style is described and characterized. The peculiarities of family educative influence on formation of some personal qualities are revealed, they are as follows: emotional stability, social courage, personal anxiety, intimacy of emotional relationships with parents, aggressiveness, indecision, disturbance and sensitivity to criticism, emotional activity, setting on a positive psychological climate. The character of the relations between the indicated variables is determined, which makes it possible to distinguish the psychological factors leading to destructive emotional development of preschool children; so psycho-correction and developmental work with rhe aim to overcome the negative factors can be further planned and implemented. The emotional positive qualities, studied with the help of experimental methods, were “emotional stability”, “social courage”, “intimacy of emotional relationships with parents”, “emotional activity”, “setting on a positive psychological climate”. It is shown that these qualities can be developed at children if they are raised in accordance with the ideas of moderation; compassion; harmonious development, and, in some cases, in the competitive and non-intervening environment. Absence of punishment inspires preschoolers to help others, to show initiative, to be active. The unfavorable factors of the emotional development were: “increased level of anxiety”, “aggressiveness”, “vulnerability and sensitivity to criticism”, “indecisiveness”. According to the results of the qualitative research, these characteristics are developed at children, whose parents use the styles of competition, prevention, control, non-interference.